Zeolit Alam Sebagai Material Coating: Uji Karakteristik Pupuk Coating dan Noncoating - Pardoyo, Pardoyo; Lestari, Siswati; Arryanto, Yateman (Jurnal Kimia Sains dan Aplikasi, 2005)
It has been intensively researched to find out the differences of coating and noncoating fertilizer characteristic. Adsorption of water evaporate, pH resistance and influence of material contact area were examined. A distinction between two material structures was analyzed with infrared spectrophotometer. The result showed that at optimum time (70 hours) increase of noncoating fertilizer weight because of water evaporate was 0,9771 gram bigger than coating fertilizer (0,8730 gram). Coating fertilizer was more resistant to pH than noncoating fertilizer. Coating fertilizer dissolved smaller than noncoating fertilizer about 0,02 gram. At the same optimum time, material, which has larger contact area, had the increase of weight bigger than material, which has smaller contact area. The IR spectra of coating fertilizer showed a peak of absorption at 532,3 cm-1 because of vibration T-O which encounter oxygen that has not been found at noncoating fertilizer spectra.Keyword: zeolite, characteristic, fertilizer, coating